Syndemic Burden in People Living with HIV: A Systematic Review and Meta-Analysis of Depression and Anxiety Across Diverse Populations - Rifki Sakinah Nompo; Dolpiana Siyoho; Meland Ibiah; Feronika Dubuaki (HM Publisher, 2025)
Introduction: People living with HIV (PLWH) experience elevated rates of depression (31%) and anxiety (28–97%), which are often embedded within broader syndemic contexts involving multiple co-occurring psychosocial stressors. However, comprehensive meta-analytic synthesis of syndemic burden across diverse populations remains limited. This review integrates evidence on the relationship between syndemic burden (cumulative psychosocial stressors) and depression/anxiety in PLWH. Methods: Systematic literature search across Scopus, PubMed/MEDLINE, and Web of Science (2000–2025). Eligible studies reported quantitative associations between psychosocial stressors and depression or anxiety in PLWH. Data were extracted independently by two reviewers. Random-effects meta-analysis using Hedges g and odds ratios (95% confidence intervals) was conducted separately for depression and anxiety. Risk of bias was assessed using the Modified Newcastle–Ottawa Scale. GRADE methodology was applied for the certainty of evidence. Results: Seven effect sizes from six studies (N≈16,598 PLWH) were included. Depression showed robust, consistent effects (k=5, SMD=0.754, 95% CI: 0.694–0.815, I²=0%, p<0.001; OR=4.12, 95% CI: 3.05–5.54), representing a moderate-to-large clinical difference (3.8–4.5 points on PHQ-9). Anxiety also demonstrated significant effects (k=2, SMD=0.671, 95% CI: 0.012–1.330, I²=82.4%, p=0.046; OR=3.88, 95% CI: 2.76–4.91), though with high heterogeneity. The pooled effect across both outcomes was SMD=0.721 (95% CI: 0.595–0.847, I²=45.3%). Effects were consistent across cross-sectional (SMD=0.730) and longitudinal (SMD=0.749) designs. All studies were rated 7–9 on the Modified NOS, indicating low risk of bias. Conclusion: Syndemic burden is substantially associated with depression and anxiety in PLWH. Depression manifests as a consistent, primary psychiatric consequence across diverse contexts, whilst anxiety severity varies by cultural and geographical factors. Integrated screening combining PHQ-9, GAD-7, and structured psychosocial stressor assessment is warranted.